Long‐distance migration is a major factor driving local adaptation at continental scale in Coho salmon. Issue 3 (24th January 2022) - Rougemont, Quentin; Xuereb, Amanda; Dallaire, Xavier; Moore, Jean‐Sébastien; Normandeau, Eric; Perreault‐Payette, Alysse; Bougas, Bérénice; Rondeau, Eric B.; Withler, Ruth E.; Van Doornik, Donald M.; Crane, Penelope A.; Naish, Kerry A.; et al.
Abstract: Inferring the genomic basis of local adaptation is a long‐standing goal of evolutionary biology. Beyond its fundamental evolutionary implications, such knowledge can guide conservation decisions for populations of conservation and management concern. Here, we investigated the genomic basis of local adaptation in the Coho salmon ( Oncorhynchus kisutch ) across its entire North American range. We hypothesized that extensive spatial variation in environmental conditions and the species' homing behaviour may promote the establishment of local adaptation. We genotyped 7829 individuals representing 217 sampling locations at more than 100, 000 high‐quality RADseq loci to investigate how recombination might affect the detection of loci putatively under selection and took advantage of the precise description of the demographic history of the species from our previous work to draw accurate population genomic inferences about local adaptation. The results indicated that genetic differentiation scans and genetic–environment association analyses were both significantly affected by variation in recombination rate as low recombination regions displayed an increased number of outliers. By taking these confounding factors into consideration, we revealed that migration distance was the primary selective factor driving local adaptation and partial parallel divergence among distant populations. Moreover, we identified several candidate single nucleotide polymorphisms associated with long‐distance migration and altitude including a gene known to be involved in adaptation to altitude in other species. The evolutionary implications of our findings are discussed along with conservation applications. Abstract : see also the Perspective by Rebekah L. Horn and Shawn R. Narum